Предмет: Алгебра,
автор: duduugu769
Выполните действия:
9х – 6 (х – 1) = 5 (х + 2).
3x (x + y + c) – 3y (x – y – c) – 3c (x + y – c)
Даю 35 баллов только быстрее решите пж.
Ответы
Автор ответа:
3
1) 9х-6(х-1)=5(х+2)
9х-6х-9=5х+10
9х-6х-5х=10+19
-2х=29 | ÷ (-2)
х = -14,5.
2) 3х(х+у+с)-3у(х-у-с)-3с(х+у-с)=
=3x²+3xy+3xc-3xy+3y²+3yc-3xc-3yc+3c²=
=3x²+3y²+3c²=3(x²+y²+c²).
Похожие вопросы
Предмет: Русский язык,
автор: bina06
Предмет: История,
автор: knadezhda7771
Предмет: География,
автор: bellav201322
Предмет: Химия,
автор: Hamrod
Предмет: География,
автор: Alyona1520